ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011 - 2014 - Tiodorma Br. Sijabat; Cut Ermiati (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2016)
The purpose of this study was to determine whether the financial ratios in Altman can explain financial distress. There are five financial ratios in Altman, which is the ratio of Net Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Tax to Total Assets (X3), Market Value of Equity to Book Value of Total Debt (X4) and Sales to Total Assets (X5). The population in this study are listed coal company in Indonesia Stock Exchange period 2011 - 2014. This study used purposive sampling method of sampling so that there are 18 companies. The data used is secondary data that is accessed from the website www.idx.co.id. The analytical method used is descriptive analysis. The results of this study for five years of observation, the financial ratios in Altman can explain financial distress in the coal company listed on the Indonesia Stock Exchange. The coal company in this study more companies to financial distress or equivalent to 56.67 % of the company.Where it can be seen from the decline in corporate earnings and some have suffered losses in recent years, the decline in the sales of the company, the amount of the costs the company the amount of debt continues to rise and stock prices continue to fall in the capital market. Keywords: Financial Ratios, Altman Z-Score Model, Financial Distress